Tolkien, Self and Other "This Queer Creature" - Chance, Jane.; SpringerLink (Online service) (New York : Palgrave Macmillan US(Imprint), 2016)
This book examines key points of J. R. R. Tolkien's life and writing career in relation to his views on humanism and feminism, particularly his sympathy for and toleration of those who are different, deemed unimportant, or marginalized-namely, the Other. Jane Chance argues such empathy derived from a variety of causes ranging from the loss of his parents during his early life to a consciousness of the injustice and violence in both World Wars. As a result of his obligation to research and publish in his field and propelled by his sense of abjection and diminution of self, Tolkien concealed aspects of the personal in relatively consistent ways in his medieval adaptations, lectures, essays, and translations, many only recently published. These scholarly writings blend with and relate to his fictional writings in various ways depending on the moment at which he began teaching, translating, or editing a specific medieval work and, simultaneously, composing a specific poem, fantasy, or fairy-story. What Tolkien read and studied from the time before and during his college days at Exeter and continued researching until he died opens a door into understanding how he uniquely interpreted and repurposed the medieval in constructing fantasy.
Introduction: "This Queer Creature" -- Chapter 1: Forlorn and Abject: Tolkien and His Earliest Writings (1914-1924) -- Chapter 2: Bilbo as Sigurd in the Fairy-Story Hobbit (1920-1927) -- Chapter 3: Tolkien's Fairy-Story Beowulfs (1926-1940s) -- Chapter 4: "Queer Endings" After Beowulf: The Fall of Arthur (1931-1934) -- Chapter 5: Apartheid in Tolkien: Chaucer and The Lord of the Rings, Books 1-3 -- Chapter 6: "Usually Slighted": Gudrún, Other Medieval Women, and The Lord of the Rings, Book 3 (1925-1943) -- Chapter 7: The Failure of Masculinity: The Homecoming of Beorhtnoth (1920), Sir Gawain (1925), and The Lord of the Rings, Books 3-6 (1943-1948) -- Conclusion: The Ennoblement of the Humble: The History of Middle-earth.
Keywords: Literature-Philosophy.; British literature; Literature, Modern-20th century; Fiction; Literature-History and criticism